An enumeration algorithm for solving the fleet management problem in underground mines - Beaulieu, Mathieu; Gamache, Michel (Computers & operations research, 2006)
This paper presents an enumeration algorithm based on dynamic programming for optimally solving the fleet management problem in underground mines. This problem consists of routing and scheduling bidirectional vehicles on a haulage network composed of one-lane bidirectional road segments. The method takes into account the displacement modes of the vehicles, either forward or in reverse, and makes sure that these vehicles move forward when they arrive at their service point. The method has been developed for the underground mine context, but it can be extended to the industrial environment. [PUBLICATION ABSTRACT]